2020
DOI: 10.1007/s40962-019-00403-3
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of Compacted Graphite Iron Near Critical Shrinkage Areas in Cylinder Blocks

Abstract: To study the microstructure of CGI near areas prone to shrinkage, a special sample was developed that resembles critical areas in cylinder blocks. Foundry trials were conducted with different magnesium contents and inoculation amounts. Using color etching techniques to follow the solidification sequence, four areas were observed with different macrostructure: (i) direct chill and columnar region near the surface; (ii) small eutectic cells and small intercellular space; (iii) large eutectic cells and large inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…It is much more difficult to find examples of research using ML tools in the analysis of CGI properties. The latest publications on this material use either qualitative analysis [42][43][44] or the traditional statistical approach to search for dependencies and build linear regression models [45,46].…”
Section: Figurementioning
confidence: 99%
“…It is much more difficult to find examples of research using ML tools in the analysis of CGI properties. The latest publications on this material use either qualitative analysis [42][43][44] or the traditional statistical approach to search for dependencies and build linear regression models [45,46].…”
Section: Figurementioning
confidence: 99%
“…Boeri et al [ 11 ] designed three different shapes of stepped specimens to evaluate the compacted graphite iron, and it was found that the shrinkage was mainly generated at the interstices of the dendritic arms. Ramos et al [ 12 ] observed the microstructure of compacted graphite iron near the shrinkage zone and found that the eutectic undercooling plays a key role in the microstructure of compacted graphite iron, as well as in the generation of shrinkage, and it was found that a decrease in the eutectic undercooling could reduce the generation of shrinkage.…”
Section: Introductionmentioning
confidence: 99%
“…In CGI production, the goal is to get as close to the eutectic solidification point as possible to get as much carbon precipitating in the form of graphite as possible to fill out the shrinkage porosity without getting any cementite or exploded graphite [4]. The narrow production process window of CGI and the unexpected parameter changes may lead to a large deviation in the treating effect of one-step graphite vermicularization.…”
Section: Introductionmentioning
confidence: 99%
“…As the last adjustment of molten iron state, inoculation will have an independent or even contradictory effect on the actual solidification morphology of the melt and the nodularity rate of graphite particles [5][6][7]. Due to a lack of knowledge about actual solidification behavior and inoculation mechanism in CGI, it is more difficult to produce sound cast components, mainly due to the control of shrinkage porosity defects [4,8]. Therefore, in CGI foundry, it is often seen that there are shrinkage porosity defects and unqualified graphite shape castings.…”
Section: Introductionmentioning
confidence: 99%